Identifikasi Tren Penelitian Efisiensi Technology Transfer Office dengan Pendekatan Bibliometrika pada Database Jurnal Scopus - Sisca Eka Fitria; Raissy Andinniya Adzanty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to identify the bibliometric characteristics of research related to factors affecting the efficiency of the Technology Transfer Office in the Scopus journal database since the beginning of the topic. The method used in this study is descriptive quantitative. This study identifies research trends, the most influential authors, documents with the most citations, the most occurring words, and other bibliometric information. The sample used was 444 publications in the form of articles and conference papers indexed by Scopus. The analysis tools used were R software version 4.3.2 and bibliometrix package version 4.1. The findings show that research interest in technology transfer efficiency continues to increase to date. Research directions show a continued focus on entrepreneurship and technological change, with additional emphasis on the role of public policy in supporting TTOs. This research contributes some information and insights into the extent to which the topic of office technology transfer efficiency is covered in articles and conference papers found in the Scopus journal database.